Strategic Interventions for Character Development in the Era of Society 5.0: A Systematic Literature Review of Indonesian Higher Education - Siregar, Tiur Malasari; Sinaga, Fajar Apollo; Hutagalung, Trisnawati; Firdaus, Muliawan; Ramadhani, Irham; Tanjung, Yul Ifda; Sihombing, Rizky Agassy (FKIP Universitas Lampung, 2025)
Strategic Interventions for Character Development in the Era of Society 5.0: A Systematic Literature Review of Indonesian Higher Education. Globalization has introduced foreign cultures that threaten students' moral integrity, making character education essential to shaping and preserving their identity. Objectives: This study analyzes strategic efforts in the campus environment as drivers of student character formation in the era of globalization. Methods: This study used a systematic literature review with a descriptive-qualitative approach to synthesize and analyze existing research on student character development. Data were collected from Google Scholar, Scopus, and ERIC databases, focusing on journal articles published over the last 10 years (2015-2025). The literature search used several databases with relevant keywords, applying inclusion and exclusion criteria based on study type, language, and publication period. From an initial search using the keyword